On the clinical relevance of using complete high-resolution HLA typing for an accurate interpretation of posttransplant immune-mediated graft outcomes - Meneghini, Maria; Perona, Anna; Crespo, Elena; Bemelman, Frederike; Reinke, Petra; Viklicky, Ondrej; Giral, Magali; Palou, Eduard; Torija, Alba; Donadeu, Laura; Melilli, Edoardo; Zuñiga, Jose; et al. (Frontiers in Immunology, 2022)
Complete and High-resolution (HR)HLA typing improves the accurate assessment of donor-recipient compatibility and pre-transplant donor-specific antibodies (DSA). However, the value of this information to identify de novo immune-mediated graft events and its impact on outcomes has not been assessed. In 241 donor/recipient kidney transplant pairs, DNA samples were re-evaluated for 6 loci (A/B/C/DRB1/DQB1+A1/DPB1) HR HLA typing. De novo anti-HLA antibodies were assessed using solid-phase assays, and dnDSA were classified either: 1) as per current clinical practice according to 3 loci (A/B/DRB1) Low-Resolution (LR) typing, estimating donor HLA-C/DQ typing with frequency tables, or 2) according to complete 6 loci HR typing. The impact on graft outcomes was compared between groups. According to LR HLA typing, 36 (15%) patients developed dnDSA (LR_dnDSA+). 29/36 (80%) were confirmed to have dnDSA by HR typing (LR_dnDSA+/HR_dnDSA+), whereas 7 (20%) did not (LR_dnDSA+/HR_dnDSA-). Out of 49 LR_dnDSA specificities, 34 (69%) were confirmed by HR typing whereas 15 (31%) LR specificities were not confirmed. LR_dnDSA+/HR_dnDSA+ patients were at higher risk of ABMR as compared to dnDSA- and LR_dnDSA+/HR_dnDSA- (logRank<0.001), and higher risk of death-censored graft loss (logRank=0.001). Both LR_dnDSA+ (HR:3.51, 95%CI=1.25-9.85) and LR_dnDSA+/HR_dnDSA+ (HR:4.09, 95%CI=1.45-11.54), but not LR_dnDSA+/HR_dnDSA- independently predicted graft loss. The implementation of HR HLA typing improves the characterization of biologically relevant de novo anti-HLA DSA and discriminates patients with poorer graft outcomes.